Konceptualna mapa wizualności - Kucner, Andrzej (Studia Europaea Gnesnensia, 2019)
The analysis conducted in this paper focuses on the issue of visuality, seeking to determine its fundamental ontological and semiotic aspects. The map of visuality referred to in the title denotes the intention to systematize the condi-tions underlying a visual image and its significance as a product of technology and culture as well as a medium of communication.